Development of On-Board In-Cylinder Gas Flow Model for Heat Loss Estimation of Diesel Engines - Mitsuhisa Ichiyanagi; Kazuki Kojima; Hayao Joji; Hiroki Matsui; Takashi Suzuki (International Journal of Industrial Research and Applied Engineering, 2018)
Diesel engines have been demanded to further increase the thermal efficiency through precise engine control under transient driving conditions, especially, it is essential to optimize the fuel injection timing and quantity cycle-by-cycle. Conventionally, fuel injection have been controlled by control maps, which resulted in large numbers of experiments and increase in cost. In order to overcome these problems, the present study focused on the model-based control and developed the on-board gas flow model, because the heat loss is affected by the turbulent intensity. Firstly, a validation of the CFD simulation is evaluated. The CFD simulation was used to validate the developed models and to determine unknown parameters used in the model. Secondly, modeling of in-cylinder gas flow is presented. To estimate the injection timing within 0.5 deg. against the target value, the heat loss must be estimated within the error range of 7.6%. Finally, as results, the error of heat loss obtained from gas flow model was 1.6%, and gas flow model fully met the requirement of tolerance range. From the viewpoint of calculation time, the calculation time of the model was 50.6 ms per cycle, and thus the model is capable of the use of on-board applications.